Comparison of Dispute Resolution in General Elections in Indonesia and Hungary - Amiludin, Amiludin; Saputra, Darwin; Prasetya Umara, Undang; Hidayatulloh, Hidayatulloh (Universitas Muhammadiyah Malang, 2024)
The purpose of this article is to provide an in-depth analysis of the electoral dispute resolution mechanisms in Indonesia and Hungary. Indonesia, the world's largest democracy, holds general elections every five years based on Law Number 7 of 2017, aiming to influence the public through non-coercive means such as rhetoric and public relations, despite the controversial use of agitation and propaganda. Various obstacles and disputes often arise, requiring effective resolution mechanisms involving multiple institutions like the Election Supervisory Board, the Supreme Court, the Honorary Council of Election Organizers, and the Constitutional Court. Hungary, a European Union member with a parliamentary system, employs a mixed electoral system combining proportional representation and single-member districts, with the National Election Committee managing complaints and objections, supported by the Election Court and the Constitutional Court. Using a normative approach with statutory, historical, and comparative legal methods, this study reveals that Indonesia's multi-tiered dispute resolution mechanism ensures comprehensive coverage but faces challenges in legal certainty and efficiency, while Hungary's centralized system offers a more efficient process but faces issues of transparency and accountability. The findings suggest that Indonesia could benefit from streamlining its approach, while Hungary might focus on enhancing the transparency of its system, providing valuable insights for refining electoral dispute resolution processes in both countries to ensure democratic integrity. Abstrak Penulisan artikel ini bertujuan untuk memberikan analisis mendalam tentang mekanisme penyelesaian sengketa pemilu di Indonesia dan Hongaria. Indonesia, demokrasi terbesar di dunia, mengadakan pemilihan umum setiap lima tahun sekali berdasarkan Undang-Undang Nomor 7 Tahun 2017, yang bertujuan untuk mempengaruhi publik melalui cara-cara non-koersif seperti retorika dan hubungan masyarakat, meskipun penggunaan agitasi dan propaganda kontroversial. Berbagai hambatan dan sengketa sering muncul, yang memerlukan mekanisme penyelesaian yang efektif yang melibatkan berbagai institusi seperti Badan Pengawas Pemilu, Mahkamah Agung, Dewan Kehormatan Penyelenggara Pemilu, dan Mahkamah Konstitusi. Hongaria, anggota Uni Eropa dengan sistem parlementer, menggunakan sistem pemilu campuran yang menggabungkan perwakilan proporsional dan distrik anggota tunggal, dengan Komite Pemilihan Nasional mengelola keluhan dan keberatan, didukung oleh Pengadilan Pemilihan dan Mahkamah Konstitusi. Menggunakan pendekatan normatif dengan metode hukum statutori, historis, dan komparatif, studi ini mengungkapkan bahwa mekanisme penyelesaian sengketa bertingkat di Indonesia memastikan cakupan yang komprehensif tetapi menghadapi tantangan dalam kepastian hukum dan efisiensi, sementara sistem terpusat Hongaria menawarkan proses yang lebih efisien tetapi menghadapi masalah transparansi dan akuntabilitas. Temuan ini menunjukkan bahwa Indonesia dapat mengambil manfaat dari penyederhanaan pendekatannya, sementara Hongaria mungkin perlu fokus pada peningkatan transparansi sistemnya, memberikan wawasan berharga untuk menyempurnakan proses penyelesaian sengketa pemilu di kedua negara guna memastikan integritas demokratis.